Colonic obstruction secondary to incarcerated transiliac bone hernia. Issue 3 (19th January 2021) - Seretis, Charalampos; Marimuthu, Kalimuthu; Piramanayagam, Balasubramaniam
Abstract: Transiliac bone hernias are a rare cause of intestinal obstruction, and high clinical suspicion is required for their diagnosis. Abstract : Transiliac bone hernias are a rare cause of intestinal obstruction, and high clinical suspicion is required for their diagnosis.